Apallic syndrome of toxic origin: the diagnostic criteria - N.V. Kurdil; A.O. Volosovets; O.V. Ivashchenko; V.S. Lisovska; H.M. Balan; O.M. Rozhkova; V.V. Andriushchenko (Медицина неотложных состояний)
Background. The global epidemic of strong synthetic opioids and “new” psychoactive substances has increased the number of overdoses that cause prolonged coma with subsequent persistent vegetative state or apallic syndrome. The purpose was to investigate the clinical manifestations, functional and pathohistological changes of the brain in apallic syndrome due to severe drug poisoning (overdose). Materials and methods. A retrospective analysis of the medical data of six people aged 21–38 years with drug poisoning involving illegal methadone, psychostimulants, barbiturates and alcohol was carried out. Results. Among the patients of the toxicology department of the Kyiv City Clinical Emergency Hospital in 2008–2020, an increase in the number of cases of apallic syndrome was noted from 0.025 to 0.14 ‰, which correlates with mass poisonings with illegal methadone. A key role in the diagnosis of apallic syndrome of toxic origin belongs to the neurological and behavioural examination of the patient, which should be carried out by experienced neurologists specialising in counselling people with poisoning. Functional magnetic resonance imaging and positron emission tomography are the modern standard for diagnosing vegetative states; however, these methods are still difficult to access in Ukraine. The visualization zones of the pathological process in the brain in case of toxic damage are mainly basal ganglia and/or thalamus and dentate nucleus, cortical zone of grey matter, periventricular zone of white matter, corticospinal tract and corpus callosum; asymmetric white matter damage as a sign of demyelination; parietal-occipital subcortical vasogenic edema and lesions of the central pons are characteristic. Forensic and histological studies of the cerebral cortex revealed diffuse loss of neurons, neuronophagia, satellitosis, deformed pyramidal neurons with apical dendrites and manifestations of homogenising necrosis, angiomatosis microfoci and neuropil vacuolation, mineralization of the tissue and a moderate glial reaction around the petrifications. Conclusions. For the health care system of Ukraine, it remains relevant to improve the existing definitions and diagnostic criteria of the apallic syndrome, which attracts the attention of doctors in connection with an increase in cases of life extension of patients after waking up from a long coma.